Identification of immunodominant epitopes of Schistosoma mansoni vaccine candidate antigens using human T cells - CT Fonseca; E Cunha-Neto; J Kalil; AR de Jesus; R Correa-Oliveira; EM Carvalho; SC Oliveira (Memorias do Instituto Oswaldo Cruz, 2004)
Paramyosin and Sm14 are two of the six antigens selected by the World Health Organization as candidates to compose a subunit vaccine against schistosomiasis. Both antigens are recognized by individuals naturally resistant to Schistosoma mansoni infection and induced protective immunity in the murine model. Three Sm14 epitopes and eleven paramyosin epitopes were selected by their ability to bind to different HLA-DR molecules using the TEPITOPE computer program, and these peptides were synthetically produced. The cellular recognition of Sm14 and paramyosin epitopes by peripheral blood mononuclear cells of individuals living in endemic area for schistosomiasis was tested by T cell proliferation assay. Among all Sm14 and paramyosin epitopes studied, Sm14-3 was preferentially recognized by individuals naturally resistant to S. mansoni infection while Para-5 was preferentially recognized by individuals resistant to reinfection. These two peptides represent promising antigens to be used in an experimental vaccine against schistosomiasis, since their preferential recognition by resistant individuals suggest their involvement in the induction of protective immunity.